The study of antibodies level to glial tumours antigens in blood of neurooncological patients - Lisyany, N. I.; Belska, L. N.; Rozumenko, V. D.; Potapova, A. I. (Ukrainian Neurosurgical Journal, 2009)
The level of antibodies to tumor tissue at patients with brain tumors was studied using enzyme-linked immunosorbent assay with tumor cells. Antibodies to antigens of glial tumors were found in the blood of neurooncological patients. The highest level of antibodies was determined in the blood of patients with glioblastoma, the lowest one — with astrocytoma of II grade of anaplasia and oligodendroglioma. A weak interaction of serum of patients with glioblastoma with antigens of astrocytoma and oligodendroglioma cells was found. A high level of antibodies to antigens of glioblastomа cells reflects the intensive Th-2 specific immune humoral answer.